Challenges and Issues in Maintaining Green Building Features and Facilities - Jasme, Nurshafarina; Au-Yong, Cheong Peng; Chia, Yi Yang; Hou, Huiying (Cynthia) (International Journal of Sustainable Construction Engineering and Technology, 2025)
The integration of green building features and facilities has received considerable attention in recent years due to their potential for reducing environmental impact and promoting sustainable practices. Despite the numerous benefits associated with green buildings, maintaining these features and facilities over time presents considerable challenges and issues. Thus, this paper aims to identify the maintenance challenges and issues within Green Building Index (GBI) certified green office buildings in Malaysia through a comprehensive literature review, questionnaire surveys and interviews. The study identifies the key maintenance challenges, assesses the likelihood and impact, and proposes effective solutions. Throughout the study, both challenges and issues highlighted that maintenance management is likely related to the financial availability of an organization and the shortage of skilled maintenance personnel. Additionally, the study emphasizes the importance of developing a comprehensive financial plan in advance as a way to investigate the efficiency and effectiveness of maintenance management and prevent budget overspending during maintenance work. By addressing this challenge, the study provides fundamental knowledge for sustaining the functionality of green buildings and ensuring their long-term viability.